Ultrasound-guided stenting in the common femoral vein for accurate stent distal landing - Yuji Hoshino, MD; Hiroyoshi Yokoi, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Objective/Background: Venous stenting has been reported with excellent clinical results; however, inadequate inflow can increase the risk of stent occlusion. When extending the stent into the common femoral vein (CFV), it is essential to ensure adequate inflow from the femoral vein, deep femoral vein (DFV), and great saphenous vein. Accurate identification of the distal landing zone (DLZ) of the stent is crucial to ensure adequate inflow. The DLZ is usually determined by venography or intravascular ultrasound (IVUS) with reference to bony landmarks. However, the uncertainty can lead to misidentification of the DLZ and inadequate stent placement, resulting in stent occlusion. Methods: From December 2016 to December 2022, 42 venous stent placements were performed in 40 patients with post-thrombotic iliofemoral vein obstruction and/or stenosis. Three patients had developed early stent occlusion owing to a misidentified DLZ. To improve accuracy in identifying the DLZ during venous stenting, ultrasound-guided placement was performed in the CFV of five patients (four on the left and one on the right) with post-thrombotic changes in the CFV and occlusion of the common iliac vein and external iliac vein. The distal end of the stent was adjusted just above the saphenofemoral junction in two cases and just proximal to the DFV confluence in three cases. Stent placement was verified using both long-axis ultrasound and fluoroscopy. Results: Ultrasound images of the CFV region provided clear visualization of the stent deployment site and accurate landmark locations, such as the saphenofemoral junction and DFV confluence, allowing for precise adjustments during stent deployment. This technique enabled easier and more definitive identification of other branches of the CFV than previously provided by IVUS and venography. No complications were observed in any of the 42 cases, and long-term patency was achieved at the final follow-up after stenting (average, 10 months; range, 3-14 months). Conclusions: Ultrasound-guided stenting in the CFV allows for real-time and accurate stent deployment with precise adjustment to the optimal DLZ. Using this technique, combined with venography and IVUS, missed distal lesions and subsequent stent occlusion can be prevented, potentially contributing to better treatment outcomes.